2014
DOI: 10.1128/jvi.02017-13
|View full text |Cite
|
Sign up to set email alerts
|

Hypervariable Region 1 Deletion and Required Adaptive Envelope Mutations Confer Decreased Dependency on Scavenger Receptor Class B Type I and Low-Density Lipoprotein Receptor for Hepatitis C Virus

Abstract: c Hypervariable region 1 (HVR1) of envelope protein 2 (E2) of hepatitis C virus (HCV) serves important yet undefined roles in the viral life cycle. We previously showed that the viability of HVR1-deleted JFH1-based recombinants with Core-NS2 of H77 (H77 ⌬HVR1 , genotype 1a) and S52 (S52 ⌬HVR1 , genotype 3a) in Huh7.5 cells was rescued by E2 substitutions N476D/S733F and an E1 substitution, A369V, respectively; HVR1-deleted J6 (J6 ⌬HVR1 , genotype 2a) was fully viable. In single-cycle production assays, where H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 53 publications
3
66
1
Order By: Relevance
“…2 and 3). These results therefore extend and refine observations previously reported by us and others (10,49) and indicate that HVR1 modulates HCV utilization of SR-BI and that Jc1 particles lacking this domain display modified SR-BI dependence during cell entry, as they are no longer neutralized by these SR-BItargeting molecules.…”
Section: Discussionsupporting
confidence: 79%
“…2 and 3). These results therefore extend and refine observations previously reported by us and others (10,49) and indicate that HVR1 modulates HCV utilization of SR-BI and that Jc1 particles lacking this domain display modified SR-BI dependence during cell entry, as they are no longer neutralized by these SR-BItargeting molecules.…”
Section: Discussionsupporting
confidence: 79%
“…Transfection of CD81-deficient S29 cells (32) for determination of intra-and extracellular HCV Core titers and infectivity titers, respectively, was carried out as previously described (54,57,58). In brief, 400,000 S29 cells were plated in 6-well plates 24 h before transfection.…”
Section: Methodsmentioning
confidence: 99%
“…10C). We used a polyclonal anti-ApoE antibody because previous studies on viruses lacking HVR1 (⌬HVR1) have shown that polyclonal anti-ApoE antibodies differently neutralize ⌬HVR1 viruses, while monoclonal anti-ApoE antibodies do not (50,76,77). As shown in Fig.…”
Section: Selection Of a Monensin-resistant Virusmentioning
confidence: 99%